Efficacy and safety of dapagliflozin monotherapy in Japanese patients with type 2 diabetes inadequately controlled by diet and exercise. Issue 11 (8th July 2014) - Kaku, K.; Kiyosue, A.; Inoue, S.; Ueda, N.; Tokudome, T.; Yang, J.; Langkilde, A. M.
<x xml:space="preserve">Abstract</x> Aims To evaluate the efficacy and safety of the selective sodium glucose co‐transporter 2 inhibitor dapagliflozin in Japanese patients with type 2 diabetes mellitus (T2DM) inadequately controlled by diet and exercise. Methods Patients received placebo or dapagliflozin (5 or 10 mg) once daily for 24 weeks. The primary outcome measure was change from baseline in glycated haemoglobin (HbA1c). Results Patients (N = 261) had modestly elevated baseline HbA1c (mean ≈ 7.5%) and most had mild or moderate renal impairment (estimated glomerular filtration rate range 43–103 ml/min/1.73 m2). Greater reductions in mean HbA1c level were observed with dapagliflozin (5 mg, −0.41%; 10 mg, −0.45%) than with placebo (−0.06%) at week 24 and these were greater in patients with higher baseline HbA1c levels. Fasting plasma glucose (FPG) was also significantly reduced with dapagliflozin (5 mg, −8.6 mg/dl; 10 mg, −13.7 mg/dl) compared with placebo (+5.8 mg/dl). Dapagliflozin significantly reduced body weight (5 mg, −2.13 kg; 10 mg, −2.22 kg) compared with placebo (−0.84 kg). Overall, 47.7 and 64.8% of patients with dapagliflozin 5 and 10 mg, respectively, and 51.7% with placebo experienced ≥1 adverse event, mostly mild or moderate, and unrelated to study treatment. Two patients on dapagliflozin 10 mg reported hypoglycaemia. Four patients across all groups reported events suggestive of genital infection and four of urinary tract infection. No events of pyelonephritis were reported. Conclusion Dapagliflozin (5 and 10 mg) was well tolerated and effective in reducing HbA1c, FPG and body weight over 24 weeks in Japanese patients with T2DM inadequately controlled by diet and exercise.